Depressão pós-parto: relação com o consumo de ultraprocessados e outros fatores - Goes, Andréa Costa (2022)
Introduction: Depression is the most prevalent psychiatric disorder in the postpartum period, the demands in the puerperium, in addition to making them more susceptible to psychological changes, can favor the consumption of ultra-processed foods in place of in natura, minimally processed foods and culinary preparations. A diet rich in fruits, vegetables, fish and whole grains appears to have a neuroprotective effect for postpartum depression. However, the risks associated with the consumption of ultra-processed foods in the puerperium are not known. Objective: To investigate the relationship between the consumption of ultra-processed foods and other factors with postpartum depressive symptoms. Methods: Cross-sectional study with 299 adult women, in the first postpartum semester, users of Primary Health Care in the city of Aracaju, Sergipe. Data collection toet al place through a telephone interview. A semi-structured questionnaire was applied with questions about obstetric history, current pregnancy, childbirth and postpartum, satisfaction with hospital/maternity care, breastfeeding, Covid-19, sleep quality, smet aling and drinking behavior, anthropometric data and socioeconomic conditions. To screen for depressive symptoms, the validated version of the Edinburgh Postnatal Depression Scale (EPDS) was applied. The percentage of energy contribution from the consumption of ultra-processed foods was calculated from two 24-hour food recalls adapted for NOVA classification, applied according to the Multiple Pass Method. Multiple logistic regression analysis with a hierarchical model was used to assess factors associated with depressive symptoms (≥ 10 EPDS points). In the statistical analyses, a significance level of 5% was considered. Results: It was observed that 39.5% of the women had depressive symptoms and the percentage of energy contribution from ultra-processed foods was 21.10%. There was no association of consumption of ultra-processed foods with depressive symptoms. The risk factors for depressive symptoms were absence of a partner (OR: 2.37; 95%CI 1.09;5.17), family history of postpartum depression (OR: 2.21; 95%CI 1.06;4 .59), health problem before pregnancy (OR: 2.33; 95%CI 1.27;4.29), unplanned pregnancy (OR: 1.78; 95%CI 1.00;3.15), absence breastfeeding in the first hour after birth (OR: 1.95; 95%CI 1.14;3.33), trauma during the pandemic (OR: 2.86; 95%CI 1.57;5.23), sleep quality poor (OR: 2.57; 95%CI 1.42;4.66), lack of sharing in meal preparation and baby care (OR: 2.25; 95%CI 1.26;4.02) . Lower family income (OR: 0.54; 95%CI 0.32;0.93) and shorter postpartum time (OR: 0.46; 95%CI 0.26;0.83) reduced the risk of symptoms depressants. Conclusion: Postpartum depression is a problem that deserves attention in postpartum care, especially among puerperal women treated at public health services. It is essential to identify early psychological changes and risk factors since prenatal care, and to provide a support network to accommodate the neuroendocrine and psychosocial changes that exist in the puerperium.